George Bacovia. A touchstone of Romanian symbolist poetry - Cristina Mirela Nicolaescu (Swedish Journal of Romanian Studies)
Romanian symbolism, whose theoretician was the poet Alexandru Macedonski, discovers its authentic and original vision only in a later stage, through George Bacovia. The greatest Romanian symbolist poet caused a mutation of structure and vision in Romanian lyric poetry. In Romanian lyric poetry, authentic Romanian symbolism gained definitive recognition in 1916 with the appearance of this volume Plumb [Lead]. It was highly acclaimed for its uniqueness, which derives from an exacerbated pessimism of life, the illustration in a hostile environment and fear of death, an interwar poet who created a lyric of deep sadness. He profoundly transformed poetic language, remaking the basic structure of poetry, especially on the syntactic level. Several types of sonorities can be distinguished in Romanian symbolism, in which, the inner music of Bacovia sounds distinctly, so different, for example, from Minulescu’s chansonette. The one that produces the unmistakable sound of Bacovian poetry is, of course, autumn, with its fatal role of turning everything it touches into a lament. Published in the interwar period, Bacovia’s volumes belong to “a later phase of symbolism”, with openings towards modernism. This paper investigates such features in two of his most known poems: “Plumb” and “Decor”. From the very beginning, Bacovia has consistently attracted the interest of critics. Consequently, numerous studies have been written about him, with scholars classifying him in various literary movements. Some, like Lovinescu, consider him a Symbolist; others, such as P. Constantinescu, see him as a Romantic. He has also been labeled an Expressionist (Ov. Crohmălniceanu, I. Negoiţescu, L. Ulici) or even a precursor of Postmodernism (Marian Popa). In truth, Bacovia embodies elements of each, following an ever-evolving and intriguing literary path. Others, including Mihai Cimpoi and Dinu Flămând, interpret him as an Existentialist, while V. Fanache views him as a Decadent poet. Despite these numerous labels and the challenges of classifying his work, Bacovia’s uniqueness remains undeniable, distinguishing him as a singular phenomenon in Romanian literature. Like most symbolist poets, Bacovia was attracted to the magic of correspondences or the technique of synaesthesia. In the spirit of Rimbaud, the Romanian poet assigned certain meanings to colors, associated them with emotional states, and expressed them in a totally new way. Grey, black, violet, yellow lose their status as simple chromatic reflexes and enter the category of affects. Bacovia took up the symbolic themes that he integrated into his work in a personal vision, with a new language, giving them unprecedented suggestiveness. In-depth readings can convey states of melancholy and anguish, the poetry captivating, at the same time, through its exasperating simplicity and the transparency of meanings, the mastery with which the poems are constructed. Repetition, expression of the inner emptiness, the whole network of parallelisms, the perfection of rhymes, the limited vocabulary (which expresses the tendency towards abstraction), the specific punctuation, the musicality and chromaticism are all trademarks of Bacovian lyricism. The analysis though, will not be limited only to the study of stylistic figures and poetic techniques, but it attempts to highlight the poetic message that emerges from his great work that goes deeper into a philosophical view. The depressive and oppressive state, suggested by the Bacovian sonorities, is accentuated further outlining the semantics of the words. The two aspects, the sound background and the semantic background, together make up a unitary, complex whole, bearing universal truths. One of the aspects of Bacovia’s rhetoric, achieved through the emphasis on imbalance, despair, and acute sadness, is irony, an important element that prevents his poetry from becoming monotonous. His creation may be limited in scope but is most surprisingly unequalled in terms of thematic and expressive inventivenss.